Failure analysis of 3Cr oil pipe body fracture - Jinzhi Wang; Yan Li; Xianren Kuang; Yaqin Ma; Jinheng Luo; Yan Long (Scientific Reports)
Abstract With the green and low-carbon development of oilfield, more and more repaired oil tube is used as oil and gas transportation pipeline, but there is a difference between the manufacturing and repairing standard of oil tube, and some problems inevitably occur in the use process. In this paper, we studied a 3Cr repaired oil tube body fracture accident that occurred in an oilfield oil and gas well. In order to determine the reason for the repaired oil tube fracture, macro-morphological analysis, magnetic particle detection, chemical composition analysis, mechanical properties analysis, metallographic analysis, scanning electron microscopy (SEM), energy spectrum analysis and corrosion product XRD analysis were used to analyze the repaired oil tube body. The results indicate that the tensile strength, yield strength, Rockwell hardness and chemical composition of the repaired oil tube material meet the requirements of the technical agreement for 3Cr low alloy steel, and the metallographic organization of the failed oil tube material is tempered sohnite, and its organizational grain size is 9.0 grade. The natural gas injected by gas lift contains oxygen and trace hydrogen sulfide, and the formation water is calcium chloride water type, which together form a high stress corrosion cracking sensitivity environment. In addition, corrosion pits and stress corrosion cracks are generated in the service process of the oil tube, which makes the bearing capacity of the oil tube decrease, and plastic fracture of the oil tube occurs under large axial load.